2022
DOI: 10.21037/atm-22-598
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical analysis of variations in the bronchus pattern of the left upper lobe using three-dimensional computed tomography angiography and bronchography

Abstract: Background: The number of sublobar resections performed is increasing, thoracic surgeons must be familiar with bronchus anatomy and preoperative planning plays an important role in predicting anatomical variations. However, there is few report showing anatomic variations of the left upper lobe (LUL) using three-dimensional computed tomography angiography and bronchography (3D-CTAB), and no in Chinese population. The present study aimed to use 3D-CTAB to describe variations of the pulmonary bronchus of LUL in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
(36 reference statements)
2
11
1
Order By: Relevance
“…However, there are only a few reports that have comprehensively summarized and classified the bronchovascular pattern of LS using 3D-CTBA. In this study, we analyzed the bronchovascular patterns of the LS and emphasized the differences between our results and those of previous reports (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, there are only a few reports that have comprehensively summarized and classified the bronchovascular pattern of LS using 3D-CTBA. In this study, we analyzed the bronchovascular patterns of the LS and emphasized the differences between our results and those of previous reports (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 67%
“…However, there are only a few studies describing anatomic variations of the lingular segment (LS) using three-dimensional computed tomography bronchography and angiography (3D-CTBA) (8). In our clinical practice, the anatomical variation of the lingular segment bronchus (LSB) does not accordant with the previous reports (9,10). Moreover, the more detailed classification and occurrence probability of the branching patterns of LSA has been rarely involved in previous studies (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 96%
“…the anatomical structures from multiple levels, angles, and adjustable fields of view in all directions so that anatomical variants, the anatomical alignment, and the locations of arterioles and veins can be detected in advance and precise target segmental resection can be better achieved. Nagashima et al and He et al used 3D reconstruction to describe the various types of variation of pulmonary segmental arteries and bronchi and also indirectly confirmed the accuracy of 3D reconstruction and its importance in pulmonary segmental surgery (14,19,20). The correct identification of intersegmental veins is central to anatomical segmental lung resection, and misinterpretation may lead to serious complications such as postoperative hemoptysis (21), so it is particularly important to fully understand the morphology of the intersegmental vessels, including rare anatomical variants.…”
Section: Discussionmentioning
confidence: 94%
“…Segmental pulmonary veins were relatively poorly predicted in a retrospective study, with an accuracy of 93.2%, and misidentification always occurred in the left upper lobe owing to its complex anatomical structures with small branch and blood vessel variations. 19 Thus, this prospective study was designed with intraoperative accuracy verification to reach a highly reliable conclusion. Ranking accuracy showed that misidentification always occurred in the right upper lobes because unrecognized arteriovenous crossover and different anatomic subtypes existed in the right upper lobes for different positions of the central veins, 20 which should be noted to avoid major bleeding due to blood vessel injury.…”
Section: Discussionmentioning
confidence: 99%